An approach to emotion recognition in single-channel EEG signals: a mother child interaction. (April 2016) - Gómez, A; Quintero, L; López, N; Castro, J
Abstract: In this work, we perform a first approach to emotion recognition from EEG single channel signals extracted in four (4) mother-child dyads experiment in developmental psychology. Single channel EEG signals are analyzed and processed using several window sizes by performing a statistical analysis over features in the time and frequency domains. Finally, a neural network obtained an average accuracy rate of 99% of classification in two emotional states such as happiness and sadness.